PCSK9 inhibitors for in-hospital treatment of patients with acute coronary syndrome and severe lipid metabolism disorders - O. L. Barbarash; N. V. Fedorova; D. Yu. Sedykh; O. V. Gruzdeva; O. N. Khryachkova; V. V. Kashtalap; A. A. Filimonova (Российский кардиологический журнал, 2020)
Aim. To assess the efficacy and safety of PCSK9 inhibitor alirocumab as part of a combination lipid-lowering therapy in patients with acute coronary syndrome (ACS).Material and methods. This prospective, open-label, single-center activetreatment study included 13 patients hospitalized due to ACS. The main inclusion criterion was nonachievement of target low-density lipoprotein cholesterol (LDL-C) values (<1,4 mmol/L) with high-intensity statin therapy prior to ACS. During the first 30 days after ACS, all patients received therapy with atorvastatin 40-80 mg/day or rosuvastatin 20-40 mg/day in combination with alirocumab 150 mg/ml (Praluent) administered by subcutaneous injection. Lipid and biochemical profiles were monitored. The first injection of the PCSK9 inhibitor was performed on days 3-5 of hospitalization, the second — after 2 weeks.Results. On admission, the median LDL-C was 4,3 [3,5;5,3] mmol/L. A day after administration, there was a decrease in LDL-C by 41,9% (median 2,5 [1,8;3,2] mmol/L; p=0,001) without a negative effect on high-density lipoproteins (HDL-C) (median 1,2 [0,8;1,4] mmol/L; p=0,270). Before the next injection, LDL-C decreased by another 8% (median 2,3 [1,1;4,1] mmol/L). A day after the second injection, a decrease in LDL-C from the baseline values was 69,8% (median 1,3 [0,7;1,5] mmol/L; p=0,010). Strengthening lipid-lowering therapy with a PCSK9 inhibitor within 30 days after ACS did not lead to clinical and biochemical deterioration.Conclusion. The use of subcutaneous 150-mg injections of alirocumab 2 times a week 30 days after ACS in patients who did not reach target LDL-C values with statin therapy, leads to a 69% decrease in LDL-C from baseline values and is safe.